2006
DOI: 10.1007/bf03327739
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in female patients with eating disorders

Abstract: Previous studies indicate that patients with eating disorders have alexithymic characteristics, as revealed by the Toronto Alexithymia Scale (TAS). The aim of the present study was to investigate the role of negative affect (anxiety and depression) in the relationship between eating disorders and alexithymia. In addition, we have evaluated whether the relationship between negative affect and alexithymia varies according to the type of eating disorder (anorexia and bulimia). Eighteen female patients and 16 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 36 publications
5
47
1
4
Order By: Relevance
“…Our findings seem to confirm this observation (Montebarocci et al 2006;Speranza et al 2007). Moreover, the results of our study seem to point out that the presence of alexithymia may be related to the presence of higher dissociative experiences and lower self-esteem.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings seem to confirm this observation (Montebarocci et al 2006;Speranza et al 2007). Moreover, the results of our study seem to point out that the presence of alexithymia may be related to the presence of higher dissociative experiences and lower self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…As some of the core aspects of the alexithymic construct, such as a difficulty distinguishing emotional states from bodily sensations, may be more characteristic of patients with EDs, it was suggested that patients with EDs may appear dramatically and deeply incapable of being in touch with their inner emotive world (Andersen 1988). As a consequence, these subjects may focus their attention on negative perceptual aspects of body, bypassing emotional experiences and leading to higher body dissatisfaction (Montebarocci et al 2006;De Berardis et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of any or all of these components indicates the presence of difficulties in emotional regulation. To a great extent, previous studies have focused on the lack of emotional awareness and understanding in this patient group, such as the large body of research that has explored rates of alexithymia in AN Kessler, Schwarze, Filipic, Traue, & von Wietersheim, 2006;Montebarocci et al, 2006;Taylor, Parker, Bagby, & Bourke, 1996). In the present dissertation, the main focus is on the link between negative affective states and eating disorder behaviour.…”
Section: Emotional Regulationmentioning
confidence: 97%
“…Studies using valid and reliable measures for the assessment of alexithymia have shown a high prevalence for this deficit in individuals with AN (Bourke et al, 1992;Cochrane et al, 1993;Montebarocci et al, 2006;Schmidt et al, 1993;Torres, Guerra, Lencastre, Brandão, & Roma-Torres, 2004). However, despite the evidence of this relationship, one main question remains unclear: are the affect regulation deficits a stable feature in AN?…”
Section: Introductionmentioning
confidence: 95%
“…In fact, several studies have recognized the cognitive impairment of emotional processing and regulation as a salient feature in AN, and as such have sought to analyse the relationship between AN and alexithymia (Bourke, Taylor, Parker, & Bagby, 1992;Cochrane, Brewerton, Wilson, & Hodges, 1993;Laquatra & Clopton, 1994;Montebarocci, Codispoti, Surcinelli, Franzoni, Baldaro, & Rossi, 2006;Schmidt, Jiwany, & Treasure, 1993;Taylor, Parker, Bagby, & Bourke, 1996). Alexithymia is an affective deficit where the main features are (a) a difficulty in identifying feelings and distinguishing emotions from physical sensations, (b) a difficulty in communicating emotional states to others, (c) a paucity of fantasy life (few dreams and fantasies) and (d) a tendency to focus on the concrete details of external events-an externally oriented style of thinking (Nemiah, Freyberger, & Sifneos, 1976;Taylor, 1994).…”
Section: Introductionmentioning
confidence: 99%